2022
DOI: 10.1002/sus2.85
|View full text |Cite
|
Sign up to set email alerts
|

High C–C cleavage efficiencies of ethanol oxidation reaction on mesoporous RhPt electrocatalysts

Abstract: Optimizing the structure of an electrocatalyst is critical to achieve its outstanding performance as well as to establish relationships between its composition and its performance. In this work, a series of mesoporous RhPt electrocatalysts (RhPt-MPS) with different compositions are designed and synthesized toward the ethanol oxidation reaction (EOR). The mesoporous structure of RhPt-MPS exposes abundant surface sites and channels for mass transfer of ethanol, and thus boosts the catalytic EOR performance. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…213 In real wastewater, there will be diverse inorganic and organic pollutants that may influence the urea electrolysis efficiency by impairing the stability of catalysts. [214][215][216] Several studies have conducted real urine electrolysis, and the experimental results suggest that catalysts work worse in alkalized urine solution than in pure alkalized urea solution, 66,[217][218][219] though the reason remains unclear. As such, future studies are suggested to identify pollutants in real urearich electrolytes and analyze the effect of potential substances on urea electrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…213 In real wastewater, there will be diverse inorganic and organic pollutants that may influence the urea electrolysis efficiency by impairing the stability of catalysts. [214][215][216] Several studies have conducted real urine electrolysis, and the experimental results suggest that catalysts work worse in alkalized urine solution than in pure alkalized urea solution, 66,[217][218][219] though the reason remains unclear. As such, future studies are suggested to identify pollutants in real urearich electrolytes and analyze the effect of potential substances on urea electrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the Pd-M alloy strategy not only reduces Pd content and the overall cost of electrocatalyst but also regulates the electronic structure of Pd based on the synthetic effect among the active components. Introducing a foreign metal into the host metal to form an alloy could trigger strong electron transfer, optimize electronic structures, and create more active sites, thus resulting in the altered adsorption energy for intermediates [94][95][96] . More importantly, in practical ECO 2 RR, the modified electronic structure of Pd helps to improve the reaction kinetics and alter the surface atom configurations, thereby optimizing the bonding strength for reaction intermediates.…”
Section: Alloyingmentioning
confidence: 99%
“…The addition of Rh can increase the yield of CO 2 production by promoting a more efficient CÀ C bond cleavage, also facilitating the removal of strongly adsorbed CO-like species. [6,7] The catalytic efficiency and selectivity of catalysts also depend on their size and shape. [8] The FC technology still suffers from the limited activity and stability of Pt nanoparticles (NPs), even for the best catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising catalysts to fully oxidize ethanol involve alloying Pt with Rh. The addition of Rh can increase the yield of CO 2 production by promoting a more efficient C−C bond cleavage, also facilitating the removal of strongly adsorbed CO‐like species [6,7] …”
Section: Introductionmentioning
confidence: 99%